A Comprehensive Review of Gastroesophageal Reflux Disease (GERD): Dynamic Mechanisms, Pathophysiology, Pharmacotherapeutic Management, and Psychosocial and Lifestyle Factors: A Literature Review - Aura Cinta Jihada; Ardian, Laurentius Johan (Journal of Diverse Medical Research: Medicosphere, 2024)
Abstact Background: Gastroesophageal Reflux Disease (GERD) is a complex gastrointestinal disorder affecting millions of people. This review discusses the dynamic mechanisms, pathophysiology, pharmacotherapy management, and psychosocial and lifestyle factors influencing GERD. The disease is characterized by acid reflux into the esophagus, causing symptoms such as chest pain, regurgitation, and difficulty swallowing. The management of GERD involves pharmacological therapy and lifestyle modifications. Psychosocial factors such as stress and anxiety exacerbate the symptoms. This review provides a comprehensive overview of GERD to assist healthcare professionals in delivering optimal care. Method: This study employed a literature review method to analyze various data related to Gastroesophageal Reflux Disease (GERD). Information was collected from several scientific databases, including Google Scholar, PubMed, Scopus, and ScienceDirect, using keywords relevant to the topic of GERD. Only articles meeting the inclusion criteria, such as being published within the last five years, providing an in-depth discussion on GERD, and written in English or Indonesian, were included in the review. Result: Gastroesophageal Reflux Disease (GERD) is a complex condition involving physiological, psychosocial, and lifestyle mechanisms. Its management requires a holistic approach that includes pharmacological therapy, lifestyle modifications, and stress management to reduce symptoms and improve patients' quality of life. Conclusion: Overall, Its management requires a holistic approach involving pharmacological therapy, lifestyle modifications, and stress management to alleviate symptoms and improve patients' quality of life. Psychosocial factors like stress and anxiety exacerbate symptoms, making it crucial to consider these aspects in treatment. By understanding the mechanisms, pathophysiology, and the impact of lifestyle factors on GERD, optimal care can be tailored to provide the greatest benefit to patients.